2017
DOI: 10.1111/bjop.12276
|View full text |Cite
|
Sign up to set email alerts
|

Virtual morality in the helping professions: Simulated action and resilience

Abstract: Recent advances in virtual technologies have allowed the investigation of simulated moral actions in aversive moral dilemmas. Previous studies have employed diverse populations to explore these actions, with little research considering the significance of occupation on moral decision-making. For the first time, in this study we have investigated simulated moral actions in virtual reality made by professionally trained paramedics and fire service incident commanders who are frequently faced with and must respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 55 publications
2
24
2
Order By: Relevance
“…In addition, recently published studies investigating moral actions in virtual reality (Francis, Gummerum, Ganis, Howard, & Terbeck, 2018;Francis et al, 2017) reported very different response patterns than those usually found in self-report assessments of moral judgments like the one used here. Generally, participants responded in virtual environments with greater utilitarian actions.…”
Section: Strength Limitations and Future Directionscontrasting
confidence: 66%
“…In addition, recently published studies investigating moral actions in virtual reality (Francis, Gummerum, Ganis, Howard, & Terbeck, 2018;Francis et al, 2017) reported very different response patterns than those usually found in self-report assessments of moral judgments like the one used here. Generally, participants responded in virtual environments with greater utilitarian actions.…”
Section: Strength Limitations and Future Directionscontrasting
confidence: 66%
“…Also, while moral dilemmas have been widely used in research, their usefulness for predicting moral behavior in real-life situations is debatable. A recent study using a virtual reality implementation of the footbridge dilemma showed that a clear majority of all participants would push the large stranger off the bridge [121,122], contradicting the 'classical' deontic response pattern found in almost all previous studies using written moral dilemmas. This disparity could indicate an unconscious moral self-deception among participants, which only comes to light when they actually have to have to take action under (more) realistic conditions [123,124].…”
Section: Limitations and Future Researchmentioning
confidence: 61%
“…Taking into account the composition and size of the bystander group is crucial in providing efficient help that maximizes individual survival. This might already be reflected in the calculations within the motivational system ( Francis, Gummerum, Ganis, Howard & Terbeck, 2017 ). Apathy in novel situations or with unknown bystanders could be the consequence of these calculations.…”
Section: The Ultimate Cause Of Bystander Apathymentioning
confidence: 86%